Delegating climate policy to a supranational authority: a theoretical assessment - Paul Pichler; Gerhard Sorger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We study the delegation of climate policy to a supranational environmental authority. We demonstrate that the authority faces a dynamic inconsistency problem that leads to welfare losses. The losses can be kept small if the mandate of the authority penalizes the local cost of emissions heavily, but puts little or no weight on the cost of climate change. The design of the authority's mandate creates another dynamic inconsistency because the countries face a recurrent incentive to modify it.
Keywords: F53; H87; O33; Q43; Q54; 330